(untitled) (PJDOL, 2023)
The current practices in E-learning institutes involve online video lecturers and student interaction with teachers by means of Moderate Discussion Board. Ever since the educational institutes/universities of Pakistan embarked on its mission of providing education by means of eLearning, it has been accepted that some form of interaction between student and lecturer was needed to supplement the published study material. The e-learning institutions of Pakistan are trying to full fill the desire of students for the need of student-teacher interactions. For this purpose they have recently started different interactive session like audio-video interactive sessions using the technology/software based from time to time.